2012
DOI: 10.1097/mpa.0b013e31822ade7e
|View full text |Cite
|
Sign up to set email alerts
|

An International Multicenter Randomized Controlled Trial of G17DT in Patients With Pancreatic Cancer

Abstract: A total of 154 patients were recruited: 79 G17DT and 75 placebo. A final analysis of the intention-to-treat population, using a proportional hazards model, stratifying by disease stage and adjusting for interim analysis, gave a hazard ratio for mortality of 0.75 (95% confidence interval, 0.51-1.10, P = 0.138; G17DT/placebo). A conventional analysis without adjustment for disease stage or interim analysis, censoring for chemotherapy and excluding protocol violators, gave median survival periods of 151 (G17DT) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 14 publications
0
52
0
Order By: Relevance
“…The treatment of 154 chemotherapy-naïve patients with advanced PDAC with G17DT led to a nearly doubled median OS time (151 days) compared to the placebo group (82 days). Again, the survival benefit was significantly dependent on the anti-G17DT response [79]. Negative results were reported by Shapiro et al [80] in advanced PDAC treatment for the combination of gemcitabine plus G17DT (median OS 5.8 months) compared to gemcitabine plus placebo (median OS 6.6 months).…”
Section: Vaccination Strategies In Pdac and Extrahepatic Btcmentioning
confidence: 66%
“…The treatment of 154 chemotherapy-naïve patients with advanced PDAC with G17DT led to a nearly doubled median OS time (151 days) compared to the placebo group (82 days). Again, the survival benefit was significantly dependent on the anti-G17DT response [79]. Negative results were reported by Shapiro et al [80] in advanced PDAC treatment for the combination of gemcitabine plus G17DT (median OS 5.8 months) compared to gemcitabine plus placebo (median OS 6.6 months).…”
Section: Vaccination Strategies In Pdac and Extrahepatic Btcmentioning
confidence: 66%
“…G17DT showed promise in PC after a phase II trial demonstrated significantly improved survival in antibody responders (~66% of patients) compared to nonresponders (Brett, et al, 2002). The phase III trial did not show a significant survival advantage associated with G17DT in an intention-to-treat analysis, but again demonstrated improved survival in antibody responders (Gilliam, et al, 2012). G17DT continues to be evaluated in gastrointestinal tumors, including those of the esophagus, stomach and colon.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…The administration of the anti-gastrin immunogen G17DT results in increased serum antibody levels and reduced tumor growth in patients with gastrointestinal malignancies [32]. A randomized, double-blind, placebo-controlled multicenter trial of G17DT was also recently performed [33]. Although, among the intention to treat (ITT) population, no significant differences in MST were detected between the PDAC patients treated with G17DT and those given the placebo, the MST of the two groups differed significantly after excluding major protocol violators and censoring for chemotherapy.…”
Section: G17dt (Gastrimmune)mentioning
confidence: 98%